Settler colonialism, race, and the law: why structural racism persists - Saito, Natsu Taylor 19XX- (Citizenship and migration in the Americas, 2020)
Racial Realities -- Unsettling Narratives -- Settler Colonialism -- Land and Indigenous Peoples -- Enslaved Labor and Strategies of Subjugation -- Emancipated? African Americans: Rights and Redundancy -- Others of Color: Inclusions and Exclusions -- Others of Color: Subordination and Manipulation -- Constitutional Protection and the Dynamic of Difference -- International Law and Human Rights -- Decolonization and Self-Determination -- Mapping New Worlds -- Conclusion -- Acknowledgements.